2016
DOI: 10.1016/j.carbpol.2016.03.016
|View full text |Cite
|
Sign up to set email alerts
|

A novel method for fabricating hybrid biobased nanocomposites film with stable fluorescence containing CdTe quantum dots and montmorillonite-chitosan nanosheets

Abstract: A method was presented for fabricating the fluorescent nanocomposites containing CdTe quantum dots (QDs) and montmorillonite (MMT)-chitosan (CS). MMT-CS/CdTe QDs nanocomposites were prepared via a simple, versatile and robust approach combination of covalent and electrostatic assembly methods (Scheme 1). The negatively charged MMT was initially modified with positively charged CS through electrostatic assembly, followed by incorporation of CdTe-QDs into the MMT-CS nanosheets by covalent connections between the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Semiconductor quantum dots (QDs) are attracting increasing attention due to their optical properties and high photostability [133]. Due to their strong tendency of oxidation and agglomeration, it is desirable to improve the compatibility and stability of this type of nanofillers in biopolymers [134]. Graphene quantum dots (GQDs) incorporated in biopolymer films have advantages such as availability, biodegradability, low price, and low production cost, making the nanocomposite films a preferred candidate for use in optoelectronics applications [135].…”
Section: Types Of Biopolymers and Nanofillersmentioning
confidence: 99%
“…Semiconductor quantum dots (QDs) are attracting increasing attention due to their optical properties and high photostability [133]. Due to their strong tendency of oxidation and agglomeration, it is desirable to improve the compatibility and stability of this type of nanofillers in biopolymers [134]. Graphene quantum dots (GQDs) incorporated in biopolymer films have advantages such as availability, biodegradability, low price, and low production cost, making the nanocomposite films a preferred candidate for use in optoelectronics applications [135].…”
Section: Types Of Biopolymers and Nanofillersmentioning
confidence: 99%
“…In figure 4(a), comparing the FTIR spectra of the hydrogels, MMT and CS, new peaks appeared at 2925 and 2855 cm −1 , which belonged to the antisymmetric and symmetric stretching vibration peak of C-H bond in -CH 2in CS [57,58]. Furthermore, the peak at 3633 cm −1 was typical for Al-OH stretching vibration at the edge of MMTNS [59] and the peak at 1602 cm −1 was the flexural vibration of N-H bond in -NH 2 in CS [60]. This result suggested that MMTNS and CS had composited together.…”
Section: Self-assembly Of Mmtns/cs Hydrogelsmentioning
confidence: 96%
“…The results also suggested that some of the hydrogen bonds in the CS structure are demolished, but new ones are formed between the functional groups of CS and Al-OH/Si-OH of MT. The peak at 1040 cm -1 indicates Si-O-Si characteristics, which corresponds to the MT structure [26]. Other related peaks to CS, such as at 1385 cm -1 (corresponds to -NH deformation and -CN vibration stretching), remained unchanged upon modification.…”
Section: Physico-chemical Characterizationmentioning
confidence: 97%